2022
DOI: 10.21776/ub.habitat.2022.033.2.15
|View full text |Cite
|
Sign up to set email alerts
|

Analysis The Effect Of Work Motivation And Competence On Employee Performance (Study On Employee’s PT JCI Padang, West Sumatera)

Abstract: This research was conducted at PT Japfa Comfeed Indonesia Unit Padang, which is an animal feed processing company the biggest and leading in the country. The study aims to describe and analyze the effect of work motivation and competence on employee performance at PT JCI Padang.The approach to this research uses probability sampling with simple random sampling technique. The sample used in this study was staff at the junior management level which numbered 47 people. This research method uses SEM-PLS (Structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The results of this study follow the results of research by Anggraini (2020), Choirunnisa & Koestiono (2022), Distyawaty (2019), Kurniasari et al (2018), Randa et al (2018), Wotulo et al (2018) who concluded that the direct contribution of competence variables to employee performance where competence is an essential supporting factor needed by an employee in working in a company, the better the competence possessed by the employee, the better the performance that the employee will produce to support activities work in the company. The results of this study are also in line with the results of Distyawaty's research (2019) Supervisory Apparatuses of the Regional Inspectorate of Central Sulawesi Province which found that it was partially proven that competence variables have a significant effect on employee performance.…”
Section: The Effect Of Competence On Employee Performancesupporting
confidence: 87%
See 1 more Smart Citation
“…The results of this study follow the results of research by Anggraini (2020), Choirunnisa & Koestiono (2022), Distyawaty (2019), Kurniasari et al (2018), Randa et al (2018), Wotulo et al (2018) who concluded that the direct contribution of competence variables to employee performance where competence is an essential supporting factor needed by an employee in working in a company, the better the competence possessed by the employee, the better the performance that the employee will produce to support activities work in the company. The results of this study are also in line with the results of Distyawaty's research (2019) Supervisory Apparatuses of the Regional Inspectorate of Central Sulawesi Province which found that it was partially proven that competence variables have a significant effect on employee performance.…”
Section: The Effect Of Competence On Employee Performancesupporting
confidence: 87%
“…Competence is an essential component of achieving personal and corporate performance (Choirunnisa & Koestiono, 2022). Appropriate career development can improve employee performance and productivity, reduce labour turnover, and increase employee promotion opportunities.…”
Section: The Effect Of Competence Mediate Career Development On Emplo...mentioning
confidence: 99%